Using Frozen Beads from a Mixture of Mesitylene and Meta-Xylene with Rupert’s Drop Properties in Cryogenic Neutron Moderators - Maksim V. Bulavin; Ivan L. Litvak (Journal of Nuclear Engineering, 2025)
An experimental study was conducted on the feasibility of using frozen beads with the properties of Rupert’s drops—solid frozen beads with enhanced strength made from a mixture of aromatic hydrocarbons—in cryogenic neutron moderators utilizing bead technology. It is demonstrated that the use of a new modification of the dosing device with a high discharge rate (approximately 6 units/s) significantly improves process efficiency. With standard pneumatic transport parameters maintained, it was possible to load solid frozen beads made from a mixture of mesitylene and meta-xylene into the cryogenic moderator chamber. The loading speed increased five-fold, while the beads remained intact during pneumatic transport.